Prova por ind??cios: uma an??lise ?? luz da infer??ncia para a explica????o mais coerente - Nardi, Ricardo Perin (2016)
This study supports the idea that circumstantial evidence makes possible to obtain the truth in criminal procedure. Therefore, we argue, first, that the truth obtained in criminal procedure doesn???t differ from the truth obtained in other branches of science, although there are certain limitations imposed by other similar weight values of the truth, such as sealing the taking of evidence by illegal terms. Having established this premise and adopting the theory of truth as correspondence, we argue that the analysis of the evidentiary argument must submit the inference to the most coherent theory of the case, which basically consists of a logical method of analysis of evidential reasoning that the hypothesis must explain more coherently the available evidence, which supports the hypothesis.